FACTORS ASSOCIATED WITH HYPERTENSION: RESULTS FROM THE INDONESIAN FAMILY LIFE SURVEY-5 IN 2014 - Rahayuningrum OI, Rahayuningrum OI; Probandari AN, Probandari AN; Sumardiyono S, Sumardiyono S (LPPM Universitas Duta Bangsa Surakarta, 2023)
Hypertension is still a serious global problem. In developing countries prevalence of hypertension increased from 18,8% in 2002 to 29,6% in 2014. Age, gender, Body mass index (BMI) and education can be the factors associated with hypertension. This study aimed to describe factors associated with hypertension in Indonesia from Indonesian Family Life Surveys (IFLS) wave 5 were conducted in 2014-2015. This crosssectional study analyzed data by using Chi2. Respondents aged > 40 years with complete information was 12.840, obtained from questionnaire-based interview and measurement. The result showed that the prevalence of hypertension was 5.426 (42,26%). The prevalence of hypertension on age 45-59 years old was 2.553 (47,05%), and women was higher 3.078 (56,73%) than men. Furthermore, the most prevalence of hypertension was on Body mass index (BMI) overweight 2.630 (48,47%). Respondents who had the higher level of education has the lowest prevalence of hypertension 425 (7,83%). All these results were statistically significant (P<0,001). The study found that middle-aged people, women, overweight, and lower level of education can be the factors increasing the prevalence of hypertension. Future intervention should emphasize to improve the promotion of healthy life style, education and inspire the population to maintain the ideal body weight.